Quasi-Experimental Analysis of Digital Media Campaigns Influencing Maternal Health-Seeking Behaviours in Rural South-Western Nigeria (Journal of Management and Social Sciences, 2026)
This study examined the influence of digital media campaigns on maternal health-seeking behaviours among women in rural South-Western Nigeria. Guided by the Uses and Gratification theory, the research explored how exposure to maternal health messages disseminated through WhatsApp, Facebook, and SMS shaped antenatal care attendance, facility-based delivery, and skilled birth uptake. Using a quasi-experimental design, 400 pregnant women and nursing mothers from six rural communities were sampled through multistage procedures. The findings revealed significant improvements in maternal health-seeking behaviours among women exposed to the campaign compared with those unexposed. Antenatal attendance, facility delivery, and skilled birth utilisation increased substantially after the 12-week intervention. The influence of digital media exposure was moderated by digital literacy, education level, and preference for voice and video-based formats over text. Despite these gains, digital exclusion and low literacy remained critical barriers to equitable participation. The study concludes that locally adapted digital campaigns, when combined with community health worker support, can effectively enhance maternal health-seeking behaviour in underserved communities. It recommends integrating multimedia health messaging in local languages and strengthening digital literacy among rural women to sustain improved maternal health outcomes.KeywordsMaternal health behaviour, digital campaigns, digital literacy, rural communities